A systematic review of future research challenges and prospects of organizational learning research in small medium size enterprises. (4th March 2018) - Chikweche, Tendai; Bressan, Alessandro
Abstract: This paper is a systematic review of studies on the implementation of organizational learning (OL) in small and medium size enterprises (SMEs). The review demonstrates the need for a flexible but inclusive approach which accommodates nuances and complexities of SMEs' dynamic operating environment and multiple stakeholders. Key findings from the study include recognition of the important role of informal and formal learning strategies, the need for a participatory approach towards learning and development of learning networks as part of communities of practices within SME clusters. Practical implications that emerge include the need for E-learning innovations that are relevant for SMEs, importance of context compatibility, the need for inclusive management practices and alignment of external training expertise with SMEs' life cycle stage. A key research implication that emerges is the need for development of measurement scales to measure the various OL themes. Future research direction opportunities are also identified.